Yahweh's coming of age - Bembry, Jason (Eisenbrauns, 2014)
Intro -- Contents -- Preface -- Introduction -- Part 1 Old Age in Biblical and Ugaritic Literature -- The Biblical Evidence -- The Ugaritic Evidence -- Part 2 Aging Yahweh -- Why Yahweh Is Not Old -- Yahweh Comes of Age -- Indexes.